2011
DOI: 10.1007/s11434-011-4519-7
|View full text |Cite
|
Sign up to set email alerts
|

The quasi-biennial and semi-annual oscillation features of tropical O3, NO2, and NO3 revealed by GOMOS satellite observations for 2002–2008

Abstract: 3 and the vertical velocity of the residual circulation (w-star), we conclude that dynamic transport is the principal factor controlling the QBO pattern of O 3 . Under the influence of vertical transport, the QBO signals of O 3 originate in the middle stratosphere and propagate downward along with the w-star anomalies over the equator. The residual circulation has a significant role in tropical regions, regardless of altitude, while in extratropical regions, dynamic effects are important in some years in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The Quasi-Biennial Oscillation (QBO) affects the circulation in the lower stratosphere and hence the species distribution (Gray and Russell III, 1999). Recently, QBO signatures in the variability of the middle to upper stratosphere NO 2 have been detected (Liu et al, 2011). We employ a commonly used monthly index, built using the mean of the zonal winds averaged from three equatorial stations (Canton islands, Singapore and Gan/Maldives) compiled by the Berlin Free University for 50 and 10 hPa.…”
Section: Multiple Regression and Proxiesmentioning
confidence: 99%
“…The Quasi-Biennial Oscillation (QBO) affects the circulation in the lower stratosphere and hence the species distribution (Gray and Russell III, 1999). Recently, QBO signatures in the variability of the middle to upper stratosphere NO 2 have been detected (Liu et al, 2011). We employ a commonly used monthly index, built using the mean of the zonal winds averaged from three equatorial stations (Canton islands, Singapore and Gan/Maldives) compiled by the Berlin Free University for 50 and 10 hPa.…”
Section: Multiple Regression and Proxiesmentioning
confidence: 99%
“…because NOx is less influenced by diurnal variations. NOx is almost entirely composed of NO and NO2 with a practically negligible contribution of NO3, in particular below about 5 hPa (Liu et al, 2011). Almost all NO is converted to NO2 during night (e.g., Dessler, 2000).…”
Section: Pathway Analysis Programmentioning
confidence: 99%
“…Along with the QBO in dynamical quantities, trace gases such as ozone show similar oscillations in the equatorial stratosphere due to the transport and/or chemistry associated with the QBO, and the corresponding ozone oscillation is thereby called the ozone QBO. Detailed vertical and temporal structures of the QBO in O3 and NO2 were revealed through Stratospheric Aerosol and Gas Experiment (SAGE) II data by Zawodny and McCormick (1991), Hasebe (1994), and Chipperfield et al (1994), and through Global Ozone Monitoring by Occultation of Stars (GOMOS) data by Hauchecorne et al (2010) and Liu et al (2011). Also Park et al (2017) showed the detailed structures of the QBO in O3, NOx, N2O, and HNO3 by analyzing Optical Spectrograph and Infrared Imager System (OSIRIS) data.…”
Section: Introductionmentioning
confidence: 99%
“…In the first run, seven proxies that could potentially affect the NO 2 distribution are used (the trend, stratospheric aerosols, solar cycle, Quasi-Biennial Oscillation -QBO, stratospheric temperature, stratospheric circulation, and El Niño-Southern Oscillation -ENSO). Following Mäder et al (2007), an iterative process was used to exclude proxies with confidence intervals below 90 %. For details, see Mäder et al (2007) and Knibbe et al (2014).…”
Section: Multiple Regression and Proxiesmentioning
confidence: 99%
“…Following Mäder et al (2007), an iterative process was used to exclude proxies with confidence intervals below 90 %. For details, see Mäder et al (2007) and Knibbe et al (2014). In this way, the degrees of freedom of the regression increase.…”
Section: Multiple Regression and Proxiesmentioning
confidence: 99%